The Cultural Competence of Educational Leaders: Developing a Conceptual Framework and Assessment Tool for Leadership Development. Issue 6 (November 2021) - Barakat, Maysaa; Lakin, Joni M.; Reames, Ellen; Kochan, Fran
The purpose of this article was to describe the foundational development of a conceptual framework for cultural competence of educational leaders based on an extensive literature review and to develop the CCEL instrument. Exploratory factor analysis (EFA) procedures were used on the data ( n = 252) to determine the psychometric properties of the CCEL and its validity and reliability. The purposefully selected participants were Master's degree students in educational leadership programs with University Council for Educational Administration institutional membership. EFA of the data revealed three factors of cultural competence: cultural beliefs and motivation, cultural skills, and cultural knowledge.